ONTOLOGICAL ATAVISMS IN THE DOMESTIC OCCUPATIONAL MEDICINE IN THE DIAGNOSIS OF OCCUPATIONAL DISEASE AND ASSESSMENT OF OCCUPATIONAL RISK - Владимир Валентинович Разумов (Медицина в Кузбассе)
In the domestic occupational pathology (medicine of labor) of the last decades, the ideas about professionally determined health disorders have undergone significant advances initiated by the reformatory innovations of the World Health Organization (WHO) and the International Labor Organization (ILO). However, in occupational pathology approaches, the fundamental concepts of occupational diseases, occupational risks, and diseases associated with work are actually based on the occupational pathology mentality of the middle of the last century; medical terminology sins with vagueness, understatement; ambiguity or inconsistency, which complicate the practical work of all links of occupational pathology support for workers in harmful working conditions.